2010
DOI: 10.1016/j.jaci.2010.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Weekly monitoring of children with asthma for infections and illness during common cold seasons

Abstract: Background-Exacerbations of childhood asthma and rhinovirus infections both peak during the spring and fall, suggesting that viral infections are major contributors to seasonal asthma morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 18 publications
7
141
1
6
Order By: Relevance
“…(6) These findings strongly suggest that there are cofactors which affect the relationship between RV infection and illness, and suggest that airway bacteria might contribute in this regard. Furthermore, a recent study found an increase in invasive pneumococcal disease during peak RV activity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…(6) These findings strongly suggest that there are cofactors which affect the relationship between RV infection and illness, and suggest that airway bacteria might contribute in this regard. Furthermore, a recent study found an increase in invasive pneumococcal disease during peak RV activity.…”
Section: Introductionmentioning
confidence: 82%
“…(6, 8) These samples were analyzed for common respiratory viruses by Respiratory Multicode Assay, EraGen Biosciences, Madison, Wisconsin. (9)…”
Section: Methodsmentioning
confidence: 99%
“…This issue is pertinent, especially in the context of evidence that asthmatics are more susceptible to develop lower respiratory viral infections [4] and that their infections are of greater severity [49]. Infections in asthmatics have also been reported to persist for longer, although this is controversial and the increase in RV-related illness may instead be a result of re-infection [4,50-53].…”
Section: Discussionmentioning
confidence: 99%
“…Cold and asthma symptom severity was scored based on a four-point scoring system (Table E2), as described previously [17]. Subjects were also trained to collect nasal mucus using a nose-blowing technique as previously described [18, 19].…”
Section: Methodsmentioning
confidence: 99%